Dye-Sensitized Solar Cells with Optimal Gel Electrolyte Using the Taguchi Design Method - Jenn-Kai Tsai; Wen Dung Hsu; Tian-Chiuan Wu; Jia-Song Zhou; Ji-Lin Li; Jian-Hao Liao; Teen-Hang Meen (International Journal of Photoenergy)
The Taguchi method was adopted to determine the optimal gel electrolyte used in dye-sensitized solar cells (DSSCs). Since electrolyte is a very important factor in fabrication of high performance and long-term stability DSSCs, to find the optimal composition of gel electrolyte is desired. In this paper, the common ingredients used in the liquid electrolyte were chosen. The ingredients then mixed with cheap ionic liquids and poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF-HFP) were added to form colloidal electrolyte (gel). The optimal composition of each materials in the gel electrolyte determined by Taguchi method consists of 0.03 M I2, 0.15 M KI, 0.6 M LiI, 0.5 M 4-tertbutylpyridine (TBP), and 10% PVDF-HFP dissolved in the acetonitrile and 3-methoxypropionitrile (MPN) solution with volume ratio of 2 : 1. The short circuit current density of 14.11 mA/cm2, the conversion efficiency (η) of 5.52%, and the lifetime of over 110 days were observed for the dye-sensitized solar cell assembled with optimal gel electrolyte. The lifetime increases 10 times when compared with the conventional dye-sensitized solar cell assembled with liquid electrolyte.